Rheumatoid Arthritis – Comorbidity and Clinical Aspects 2018
DOI: 10.1136/annrheumdis-2018-eular.6141
|View full text |Cite
|
Sign up to set email alerts
|

AB0330 Osteoporosis, sarcopenia and osteosarcopenia in women with rheumatoid arthritis

Abstract: BackgroundRheumatoid arthritis (RA) is a systemic inflammatory disease associated with polyarthritis, progressive joint damage, and physical impairment that can lead to osteoporosis and sarcopenia, increasing the risk of fractures and leading to a greater loss of autonomy in RA patients.ObjectivesTo assess frequency of osteoporosis, sarcopenia and osteosarcopenia in women with RA.Methods40 female patients with RA (mean age 63±7 years) and 40 female controls without RA (mean age 64±9 years) were enrolled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…We found ten cross-sectional studies ( n = 40–457 RA patients) that specifically sought to evaluate the prevalence of sarcopenia in established RA. 7079…”
Section: Alterations In Body Composition In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…We found ten cross-sectional studies ( n = 40–457 RA patients) that specifically sought to evaluate the prevalence of sarcopenia in established RA. 7079…”
Section: Alterations In Body Composition In Rheumatoid Arthritismentioning
confidence: 99%
“…We found ten cross-sectional studies (n = 40-457 RA patients) that specifically sought to evaluate the prevalence of sarcopenia in established RA. [70][71][72][73][74][75][76][77][78][79] Although sarcopenia seems to be more frequent in RA patients compared with controls, 15,16,63,64,66 it is difficult to provide conclusive evidence since the studies used different definitions for sarcopenia and involved different populations. In a cross-sectional study of 123 Moroccan RA patients (women: 87%; mean disease duration: 9.8 years; patients receiving csDMARDs: 90.2%; patients receiving bDMARDs: 8.1%), 70 the prevalence of sarcopenia was reported to be 39.8% (using the criteria proposed by Baumgartner et al 48 ), but muscle strength and physical performance were not evaluated.…”
Section: Sarcopenia In Patients With Ramentioning
confidence: 99%
“…Several cross-sectional studies have shown a higher prevalence of sarcopenia in patients with rheumatoid arthritis (RA) compared to healthy controls [20][21][22][23][24][25]. The prevalence of sarcopenia described in studies in patients with RA ranges from 7.8% [26] to 87.5% [24].…”
Section: Sarcopenia and Rheumatoid Arthritismentioning
confidence: 99%
“…Confavreux et al [ 43 ] revised the systemic bone effects of biologic therapies in IMRDs (such as RA and ankylosing spondylitis). Feklistov et al [ 22 ] observed osteoporosis (low BMD) in a cross-sectional study among 48% of women with RA versus 45% in healthy controls. Sarcopenia (muscle mass, strength, and physical performance) was observed in 25% of RA patients, and osteosarcopenia (sarcopenia + low BMD) was found in 15%, versus 12.5% and 5% in healthy controls, respectively.…”
Section: Sarcopenia and Immuno-mediated Rheumatic Diseasesmentioning
confidence: 99%